Brownification Effects from Surface Water Sources to Intelligent Rainwater Harvesting System - Musa, Sabariah (International Journal of Integrated Engineering, 2019)
Rainwater harvesting (RWH) system has gained recognition as a sustainable means to cope with water crisis in the future. This study was to evaluate RWH system in Tun Dr Ismail (TDI) College, Universiti Tun Hussein Onn Malaysia (UTHM). Since being launched at 2007, the system emerged needing of improvisation due to rusty water and incomplete system installed. Main focused was on system effectiveness to supply non-potable water (toilet flushing) and brownification factors. Three samples were collected to analyse its concentration of iron (Fe) and pH. Rainfall data from Research Centre of Soft Soil Malaysia (RECESS), UTHM and Department of Irrigation and Drainage Malaysia (DID) used to estimate capacity effectiveness of the system. Result indicated Fe does contribute to brownification process. 20 feet pipe had highest concentration of Fe at 2.25 mg/l, while a projection at week 8 could reach until 3.25 mg/l. Growth of Fe over time would cause harm to residents. As for capacity, RWH system could cover 20 days toilet usage and save up to minimum 840 MYR monthly bills, which showed great potential to be considered as alternative water supply.